Nucleus-nucleus potential with repulsive core and elastic scattering. Part 1. Nucleus-nucleus interaction potential - O. I. Davidovskaya; V. Yu. Denisov; V. O. Nesterov (Ядерна фізика та енергетика)
Various approaches for nucleus-nucleus interaction potential evaluation are discussed in details. It is shown that the antisymmetrization of nucleons belonging to different nuclei and the Pauli principle give the essential contribution into the nucleus-nucleus potential at distances, when nuclei are strongly overlapping, and lead to appearance of the repulsive core of nucleusnucleus interaction at small distances between nuclei.